1986
DOI: 10.3758/bf03330541
|View full text |Cite
|
Sign up to set email alerts
|

Context effects in word identification and episodic recognition: A single dissociation

Abstract: Two experiments were conducted to evaluate the role of context in word identification and episodic recognition. Each experiment involved a study phase and a test phase. During the study phase, subjects were presented with a mixture of scrambled, semantically anomalous, and semantically integrated sentences. During the test phase, subjects were presented with individual printed words and were required to answer either an episodic-recognition test (Experiment 1) or a wordidentification test (Experiment 2). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
1
1
0
1
Order By: Relevance
“…This finding is consistent with the decrease in memory performance found in control human subjects when tested with a variety of tasks and under different types of context manipulations (Canas and Nelson, 1986; Cann and Ross, 1989; Dalton, 1993; Emmerson 1986; Geiselman and Bjork, 1980; Hollingworth, 2006; Light and Carter-Sobel, 1970; Park et al, 1984, 1987; Reder et al, 1974; Russo et al, 1999; Smith, 1985; Smith and Vela, 1986; Stumpfel and Kirsner, 1986; Tulving and Thompson, 1973;). Furthermore, the results parallel those reported in animal studies (Dellu et al, 1997; Dix and Aggleton, 1999; Mumby et al, 2002; O'Brien et al, 2006) that have used incidental recognition memory tasks similar to the VPC-context task used in the present study.…”
Section: 0 - Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with the decrease in memory performance found in control human subjects when tested with a variety of tasks and under different types of context manipulations (Canas and Nelson, 1986; Cann and Ross, 1989; Dalton, 1993; Emmerson 1986; Geiselman and Bjork, 1980; Hollingworth, 2006; Light and Carter-Sobel, 1970; Park et al, 1984, 1987; Reder et al, 1974; Russo et al, 1999; Smith, 1985; Smith and Vela, 1986; Stumpfel and Kirsner, 1986; Tulving and Thompson, 1973;). Furthermore, the results parallel those reported in animal studies (Dellu et al, 1997; Dix and Aggleton, 1999; Mumby et al, 2002; O'Brien et al, 2006) that have used incidental recognition memory tasks similar to the VPC-context task used in the present study.…”
Section: 0 - Methodssupporting
confidence: 83%
“…It can be as simple as the color of text on a word list, or as complex as the physical environment in which learning took place. Several studies in humans have demonstrated a decreased memory performance when context is changed between encoding and retrieval after changing semantic (Light and Carter-Sobel, 1970; Reder et al, 1974; Stumpfel and Kirsner, 1986; Tulving and Thompson, 1973), cue specific (Dalton, 1993; Hollingworth, 2006; Park et al, 1984, 1987; Russo et al, 1999; Smith and Vela, 1986), olfactory (Cann and Ross, 1989), auditory (Geiselman and Bjork, 1980) or environmental (Canas and Nelson, 1986; Emmerson, 1986; Smith, 1985; Smith and Vela, 1986) contexts. Further, both rodent (Dellu et al, 1997; Dix and Aggleton, 1999) and primate (Pascalis et al, 2009) studies have shown that, although animals are able to recognize objects in a changed background context, recognition memory was stronger when the familiar context was used in the retrieval phase.…”
Section: -Introductionmentioning
confidence: 99%
“…Ce contexte est encode avec les informations et sert d'indice pour les recouvrer (Tulving, 1985). De plus, les variations contextuelles ont une influence sur la memorisation des informations (Stumpfel et Kirsner, 1986). Selon cette classification, la memoire la plus affectee lors du vieillissement semble bien-etre la memoire episodique (Smith et Fullerton, 1981).…”
unclassified